HUBUNGAN ANTARA KARAKTERISTIK INDIVIDU DAN INTRINSIK DENGAN STRES KERJA PADA PEKERJA SANDBLASTING - Anita Dewi Anggraeni; Yuliani Setyaningsih; Suroto Suroto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Job stress is a physical and emotional disturbance as a result of a mismatch between capability, resources, or the needs of workers coming from the work environment. Sandblasting is a method to clean surfaces of contaminant materials such as rust, paint, salt, oil, etc. or to obtain a material profile character for both rough and smoothing, this method is often applied to metal-based surfaces. The purpose of this study was to analyze the relationship between individual characteristics, work intrinsic, and work organization with work stress. This study uses cross sectional study which is a form of observational study and is analytic descriptive. The population of the research was sandblasting workers, amounting to 47 people with sampling method. Work stress was measured using a human-A questionnaire measured subjectively. Statistical analysis using chi-square test. The results showed no relationship between age (p-value = 1,000), education (p-value = 0.648), work period (p-value = 1,000), blood pressure (p-value = 0.362), income (p-value = 0,192), workload (p-value = 0,188), noise (p-value = 1,000), work climate (p-value = 0,141), and social support (p-value = 0,017) with job stress. Companies should redesign the breaks to reduce workload